(untitled) (Fiep Bulletin - online, 2014)
Introduction: The Pilates method is a program of physical and mental training that strengthens the mind and body as one unit. The method is widely used by many professionals, both those who work in the training of athletes as well as in the prevention and treatment of musculoskeletal disorders. Objective: To characterize the socio-economic profile of the Pilates method in Lages / SC. Methods: A descriptive cross-sectional sample of 33 active professionals. Instrument was a questionnaire socio-economic with open and closed questions. Results: Most professionals are physiotherapists. The average investment in the Studio is R 15,000.00, the average tuition charged for two hours a week is R 151.00, the average weekly income of working professionals is R 2,000.00. Conclusion: The use of the Pilates method has been growing rapidly, we need studies on the socio-economic profile elsewhere in the country compared to the numbers practiced in Lages/SC.